Number of human protein interactions correlates with structural, but not regulatory conservation of the respective genes - Mekic, Rijalda; Zolotovskaia, Marianna A.; Sorokin, Maksim; Mohammad, Tharaa; Shaban, Nina; Musatov, Ivan; Tkachev, Victor; Modestov, Alexander; Simonov, Alexander; Kuzmin, Denis; Buzdin, Anton (Frontiers in Genetics, 2024)
The differential ratio of nonsynonymous to synonymous nucleotide substitutions (dN/dS) is a common measure of the rate of structural evolution in protein-coding genes. In addition, we recently suggested that the proportion of transposable elements in gene promoters that host functional genomic sites serves as a marker of the rate of regulatory evolution of genes. Such functional genomic regions may include transcription factor binding sites and modified histone binding loci.Here, we constructed a model of the human interactome based on 600,136 documented molecular interactions and investigated the overall relationship between the number of interactions of each protein and the rate of structural and regulatory evolution of the corresponding genes. By evaluating a total of 4,505 human genes and 1,936 molecular pathways we found a general correlation between structural and regulatory evolution rate metrics (Spearman 0.08-0.16 and 0.25-0.37 for gene and pathway levels, respectively, p<0.01). Further exploration revealed in the established human interactome model lack of correlation between the rate of gene regulatory evolution and the number of protein interactions on gene level, and weak negative correlation (~0.15) on pathway level. We also found a statistically significant negative correlation between the rate of gene structural evolution and the number of protein interactions (Spearman -0.11 and -0.3 for gene and pathway levels, respectively, p<0.01). This suggests stronger structural rather than regulatory conservation of genes whose protein products have multiple interaction partners.